2018
DOI: 10.1007/s11031-018-9684-4
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in emotion regulation moderate the associations between empathy and affective distress

Abstract: Individual differences in empathy can have positive and negative psychological outcomes. Yet, individual differences in the processing and regulation of empathy-induced emotion have not been fully explored within this dynamic. This study was designed to explore whether individual differences in emotion regulation strategies moderated the effects of empathy on common forms of affective distress. Eight hundred and forty four participants completed survey measures of trait empathy, emotion regulation strategies, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
81
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(96 citation statements)
references
References 47 publications
13
81
0
Order By: Relevance
“…Although previous studies shown differences in empathy for pain skills in case-control designs in different psychiatric and neurological populations 9,[55][56][57][58][59][60][61][62][63][64][65][66][67] , no studies have revealed that individual differences in empathy for pain can predict mental symptoms. However, as in previous reports 9,68 , empathy correlated with emotion recognition in females. Arguably, the preponderant predictive effect of emotion recognition in mental symptoms manifestation could mask the role of empathy in predicting mental symptoms.…”
Section: Discussionsupporting
confidence: 86%
“…Although previous studies shown differences in empathy for pain skills in case-control designs in different psychiatric and neurological populations 9,[55][56][57][58][59][60][61][62][63][64][65][66][67] , no studies have revealed that individual differences in empathy for pain can predict mental symptoms. However, as in previous reports 9,68 , empathy correlated with emotion recognition in females. Arguably, the preponderant predictive effect of emotion recognition in mental symptoms manifestation could mask the role of empathy in predicting mental symptoms.…”
Section: Discussionsupporting
confidence: 86%
“…During the preparation of this manuscript, a study by Powell (2018) was published, which reported the same relationships between reappraisal use and trait cognitive and affective empathy in a large UK sample. The findings of our study provide further support for this recent work by replicating the findings twice, including in a sample from two countries, and demonstrating that the relationships between cognitive/affective empathy and reappraisal use are significantly different.…”
Section: Discussionmentioning
confidence: 84%
“…Finally, even if participants attend to relevant information, they can reappraise its meaning—for instance, by altering perceptions of severity, need, and responsibility (for discussion, see Zaki, ). Studies find varying evidence for the relationship between trait reappraisal and empathic emotions (Halperin & Gross, ; Lebowitz & Dovidio, ; Powell, ); other studies find that high trait reappraisal associates with a reduced link between empathy and prosocial behavior (Lockwood, Seara‐Cardoso, & Viding, ), and that reappraisal reduces empathy under certain conditions (Cameron & Payne, ). Indeed, some suggest that the “objectivity” instructions contrasted against empathy in classic empathy‐altruism studies—which encourage people to be detached and non‐emotional in response to others' suffering—might act as a regulation or reappraisal manipulation, reducing empathy compared to baseline (McAuliffe, Forster, Phillippe, & McCullough, ), which suggests that people might be quite adept at distancing themselves from feelings of empathy for others.…”
Section: A Motivated Emotion Regulation Approach To Empathymentioning
confidence: 99%